2020
DOI: 10.1371/journal.pone.0232421
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation outcomes in adults: A scoping review

Abstract: Cochlear implantation has become known as "the treatment of choice" for adults with severe to profound hearing loss. Wide variability exists, however, in the way hearing loss severity is measured and in the candidacy criteria used to recommend cochlear implantation. ObjectivesThis study aimed to provide a descriptive analysis of recent evidence available in the literature in relation to the efficacy of unilateral cochlear implantation in adults, the general findings of these studies, and the populations to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
136
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(194 citation statements)
references
References 44 publications
11
136
1
4
Order By: Relevance
“…Despite the initial introduction in 1957 and commercialization, CI became widely used in the last 20 years to provide auditory rehabilitation to individuals having severe to profound SNHL (Macherey and Carlyon, 2014;Eshraghi et al, 2017;Sousa et al, 2018;Boisvert et al, 2020;Sharma et al, 2020). The most distinguishing feature between CI and hearing aids is that hearing aids merely amplify sounds so that they can be detected by the remaining inner ear hair cells in a patient with mild to moderate hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the initial introduction in 1957 and commercialization, CI became widely used in the last 20 years to provide auditory rehabilitation to individuals having severe to profound SNHL (Macherey and Carlyon, 2014;Eshraghi et al, 2017;Sousa et al, 2018;Boisvert et al, 2020;Sharma et al, 2020). The most distinguishing feature between CI and hearing aids is that hearing aids merely amplify sounds so that they can be detected by the remaining inner ear hair cells in a patient with mild to moderate hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extending the results of the present study to the whole length of the cochlea, we suggest that even a small change in tissue density in RC could disproportionately affect electrical stimulation of the AN along the entire cochlea. Hence, reported inconsistencies in the performance of CIs [ 87 , 88 , 89 ] could be partially attributed to the eventual degeneration of (heterogeneous) neural tissues in RC and perhaps even the generation of aneural tissue. A few in-silico studies have proposed patient-specific and fully automated models to aid CI surgery and evaluation [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, six months after implantation the patients showed excellent improvements in Dantale scores and moderately to excellent improvements in HINT scores. Collecting data from 24 countries on 5 continents, a recent systematic review concluded that 82% of postlingually hearing impaired adult CI recipients achieved a speech perception improvement on the implanted ear of at least 15 percentage points [13]. In addition, the authors found that the weighted average for improvement in quality of life was 21.5 percentage points.…”
Section: Discussionmentioning
confidence: 99%